Kebijakan Pengembangan Bidang Kepemudaan dalam Tata Kelola APBDes - Arifin, Nur Zaid Ibnu; Shihab, M. Quraish; Hadiyati, Siti Fadhilah Nur (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2021)
This study seeks to describe how the political configuration of the Kedungturi Village Government's budget for the development of the youth sector through the 2018 APBDes and 2019 APBDes and how youth is involved in the drafting meetings of the RAPBDes in Kedungturi Village. The research method uses descriptive and literary qualitative using Wildavsky's political budget theory, namely sharing and sharing process. The results of this study found that there was a political configuration of the village government budget for the development of youth organizations. The sharing and bargaining process is carried out jointly through the village musrenbang forum; a system for absorbing the aspirations of preparing the RAPBDes. Through deliberations, the village government and the community expressed opinions regarding the alignment of the budget in the field of youth development through the Village Youth Organization organization. As a result, the village government determines the APBDes for the 2018 Fiscal Year and the APBDes for the 2019 Fiscal Year with an increased budget allocation in the youth sector, namely IDR 53,579,467 in 2018 and IDR 76,669,000 in 2019.